Preparation and characterization of multiwalled carbon nanotube/WO3 composite materials. Issue 12 (4th October 2013) - Vass, Adam; Berki, Peter; Nemeth, Zoltan; Reti, Balazs; Hernadi, Klara
<x xml:space="preserve">Abstract</x> Multiwalled carbon nanotube (MWCNT)/tungsten trioxide (WO3) composites were prepared by two different impregnation methods. Tungsten (VI) chloride (WCl6) was chosen as precursor compound to cover the surface of MWCNTs using either a simple or a combined impregnation technique. The applied mass ratio of MWCNT:WO3 was 1:15 for each sample. Two different temperatures (450 and 700 °C) were applied during the calcination process depending on the type of the synthesis method. The produced composite materials and the reference WO3 sample were characterized by transmission and scanning electron microscopies, Raman microscopy, and X‐ray diffraction. The results show that using varying both solvents and methods has a significant effect on the formation of composite materials. As prepared MWCNT‐based composites are planned to be applied in gas sensing techniques or in photocatalytic processes in the near future.